NILAI PENDIDIKAN ISLAM PRESPEKTIF KH. SALAHUDIN WAHID - Saefrudin, Saefrudin (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2020)
ABSTRACTChanges in education in modern society in the era of the expectation that is in accordance with the needs of the community, especially to meet the needs in the field of education through the inculcation of Islamic values in the teaching and learning process of students. Islamic education is expected to be an education that is not only as knowledge but Islamic education must be able to be applied to personal learners to the fullest as Muhaimin said that Islamic education that is currently underway in several Islamic educational institutions is more dominant in the transfer of knowledge, while the practical aspects are not serious maximum attention. the transfer of knowledge is very important but far more important is the practice of science itself through Islamic values.Basically, Islamic education is sourced from the Al-Qur'an and Hadith therefore a person who wants to develop the concept of Islamic education must base on the Al-Qur'an and Hadith in an Islamic-based educational institution starting from the stake holders of existing Islamic educational institutions, Therefore, in applying Islamic education there must be Islamic values that must be carried out continuously, so that Islamic education can be applied by stakeholders in Islamic-based institutions, so that these values can become a culture that must be implemented in the environment of Islamic education institutions with such institutions can be good and advanced in the eyes of society or government.Studying KH. Salahudin Wahid Hasyim in the concept of Islamic education, he tried to present the concept of Islamic education through Islamic values that originate from the Qur'an and hadith, such as sincerity, honesty, responsibility, hard work and tolerance (tasamuh). These values must be implemented in the world of Islamic education and Islamic education institutions. Islamic education which is based on the values of the Koran and Hadith provides an opportunity for all students to be directly involved in developing their abilities and talents, so that students are able to become good human beings, have good morals and have active, creative and innovative abilities in accordance with values - the value of good Islamic education.Â Â Keywords: Islamic Education Value, KH. Salahudin Wahid